Hindu Marriage: An Aspect of the Atharva Veda - Ishita Chakraborty (IAHN-TP Palangka Raya, 2023)
Marriage is very important among all the sa?sk?ras in ?rya life. Among the various reforms in the Gr?hya S?tras, Dharma S?tras, Smiri ??stra , the marriage reform was prepared in the desire to preserve the socialism of ?rya life. S?sk?ra in the hindu community is sometimes 10, sometimes 12, sometimes 18, sometimes more. But marriage is the most important in all Gr?hya ??tras. It is no exaggeration to call it a major reform of domestic life. In the 10.85 s?kta of Rgveda popularly known as S?ry? s?kta deals with marriage. There are 47 mantras. Mantras are chanted differently in various marriage rituals. Marriage rituals are discussed in the five sections of the first chapter of ??val?ya?a Gr?hyas?tra (5,6,7,8, 9). In the fifth chapter, ??val?ya?a will says that, first of all we have to look about the bride’s kula that is about her family , her pedigree. “kulamagre par?k?eta ye matr?ta? pitr?ta?ceti” (A?. 1/5/1). Atharvaveda sa?hit? has many more mantras besides the two marriage s?ktas and the Rgveda mantras in the 14th stanza. The first s?kta has 64 mantras, the second s?kta has 75 mantras. total 139 mantras. Their use in various rituals according to Kausika S?tra. From pedigree test to marriage finally caturth?ma?gal and to see Dhruvat?r? , keeping the family together, the importance of daughters to keep the joint family together – all are discussed. And as usual sayan’s commentary is missing. After checking the sings of prospective bride and groom, the marriage is arranged. ??str?c?ra, lok?c?ra, Gr?madharma, Janapadadharma are to be observed simultaneously. On this occasion lighting a fire, placing a pitcher full of water in the north-east, circumambulating (saptapad?) him. Bride can touch the rock (sil?) by foot. Circumambulation of the fire. L?jkhai homa, throwing ?jya into the fire, saptapad?gamana, arriving at the wedding hall, showing Druva nak?arta, Arundhati nak?arta and saptar?imandal in the sky, sitting on cowhide, then homa, eating card, applying ?jya on the body. After three days of Brhmacarya and lying on the ground, then on the fourth day donating weeding clothes to Br?hmins. Most of have to be organized. In the Atharvaveda the mantras are much more consistent and also much more numerous. Although its significance has lass important today, this institution (marriage) is ideologically important enough to reflect the ideals of ?rya caste togetherness in domestic life.